Lower limb deep vein thrombosis in COVID-19 patients admitted to intermediate care respiratory units. Issue 197 (January 2021) - Pancani, Roberta; Villari, Liliana; Foci, Valentina; Parri, Giulia; Barsotti, Francesco; Patrucco, Filippo; Malerba, Mario; Vincenti, Rigoletta; Carrozzi, Laura; Celi, Alessandro
Abstract: COVID-19 has been associated with an increased risk of thrombotic events; however, the reported incidence of deep vein thrombosis varies depending, at least in part, on the severity of the disease. Aim of this prospective, multicenter, observational study was to investigate the incidence of lower limb deep vein thrombosis as assessed by compression ultrasound in consecutive patients admitted to three pulmonary medicine wards designated to care for patients with COVID-19 related pneumonia, with or without respiratory failure but not requiring admission to an intensive care unit. Consecutive patients admitted between March 27 and May 6, 2020 were enrolled. Patients were excluded if they were less than 18-year-old or if compression ultrasound could not be performed for any reason. Patients were assessed at admission (t0) and after 7 days (t1). Major and non-major clinically relevant bleedings were recorded. Sixty-eight patients were enrolled. Two were excluded due to anatomical abnormalities that prevented compression ultrasound; sixty patients were retested at (t1). All patients were started on antithrombotic prophylaxis, unless therapeutic anticoagulation was required. Deep vein thrombosis as assessed by compression ultrasound was observed in 2 patients (3%); one of them was later deemed to represent a previous episode. No new episodes were detected at t1. One major and 2 non-major clinically relevant bleedings were observed. In the setting of patients with COVID-related pneumonia not requiring admission to an intensive care unit, the incidence of deep vein thrombosis is low and our data support not screening asymptomatic patients. Highlights: COVID-19 is characterized by increased risk of thrombotic events. Compression ultrasound is an easy and reliable method to detect deep vein thrombosis. The incidence of deep vein thrombosis in our COVID-19 patients not in ICU is very low. Screening for deep vein thrombosis in these patients is not warranted.